Replication data for "Caledonian reactivation and reworking of Timanian thrust systems and implications for latest Mesoproterozoic to mid-Paleozoic tectonics and magmatism in northern Baltica" - Koehl, Jean-Baptiste P. (DataverseNO, 2024)
Replication data for "Caledonian reactivation and reworking of Timanian thrust systems and implications for latest Mesoproterozoic to mid-Paleozoic tectonics and magmatism in northern Baltica". The dataset includes the following: -Figure 1a: Figure 1. ( a) Elevation map of the Barents Sea, northern Norway and northwestern Russia showing major structural elements from the Norwegian Offshore Directorate (thin white lines) and major fault trends in the Barents Sea (Timanian; yellow lines). The location of ( a) is shown as a red rectangle in the upper inset map and the location of ( b) as a black rectangle. The basemap and the upper inset are from Jakobsson et al. (2012). A Polar Stereographic projection was used (datum: WGS84). Abbreviations: AFC: Asterias Fault Complex; AKTW: Alta–Kvænangen tectonic window; BaFZ: Baidaratsky Fault Zone; BB: Bjørnøya Basin; BFC: Bjørnøyrenna Fault Complex; BP: Bjarmeland Platform; CTF: Central Timan Fault; ETF: East Timan Fault; FG: Forlandsundet Graben; FP: Finnmark Platform; FSB: Fingerdjupet Sub-Basin; FTB: Fold-and-Thrust Belt; HB: Harstad Basin; HfB: Hammerfest Basin; HFC: Hoop Fault Complex; JFC: Jason Fault Complex; KCFZ: Kongsfjorden–Cowanodden fault zone; KDFZ: Kinnhøgda–Daudbjørnpynten fault zone; LH: Loppa High; MB: Maud Basin; MFC: Måsøy Fault Complex; MFZ: Molloy Fracture Zone; MH: Mercurius High; NB: Nordkapp Basin; ND: Norsel Dome; NH: Norsel High; OB: NP: Nordkinn Peninsula; Olga Basin; PSP: Polhem Sub-Platform; RFC: Ringvassøya Fault Complex; RP: Rybachi Peninsula; SaD: Samson Dome; SeFZ: Senja Fracture Zone; SD: Sredni Peninsula; SFZ: Spitsbergen Fracture Zone; SH: Stappen High; SIP: Seiland Igneous Province; SISZ: Sørøya–Ingøya shear zone; SkB: Sørkapp Basin; SR: Senja Ridge; SRFZ: Sredni–Rybachi Fault Zone; SvB: Sørvestnaget Basin; SvD: Svalis Dome; TFFC: Troms–Finnmark Fault Complex; TKFZ: Trollfjorden–Komagelva Fault Zone; TyB: Tiddlybanken Basin; TøB: Tromsø Basin; VH: Veslemøy High; VKSZ: Vimsodden–Kosibapasset Shear Zone; VP: Varanger Peninsula; WTF: West ...